Tacrolimus outcomes in adult kidney transplants: a decade review - Lolita Lolita; Isrovanigoro Isrovanigoro; Metalia Puspitasari; Zijie Wang (Intelektual Pustaka Media Utama, 2026)
Tacrolimus remains a principal immunosuppressive agent in kidney transplantation, yet its reported efficacy and safety vary due to differences in study design, treatment regimens, and patient characteristics. Objectives: To summarize recent evidence on the clinical performance of tacrolimus in adult kidney transplant recipients and identify factors contributing to variability in outcomes. A narrative review was conducted using PubMed as the primary database because of its comprehensive indexing of clinical and pharmacological studies relevant to transplant immunosuppression. Additional databases were screened to ensure completeness. Studies published between 2015 and 2025 were searched using predefined keywords. Of 91 open-access articles identified, 19 met the inclusion criteria and were analyzed. Results: Reported clinical outcomes demonstrated wide variability across studies. Acute rejection ranged from 0-18.8%, while biopsy-proven acute rejection varied substantially (0-85%). Graft loss occurred in 0-15% of recipients and mortality in 0-8%. Major adverse events were also heterogeneous, including cytomegalovirus (CMV) infection (0-16.9%), new-onset diabetes after transplantation (NODAT) (0-22.8%), and tremor (3-28.6%). Variability in findings was largely influenced by differences in study methodology, concomitant immunosuppressive protocols, monitoring practices, population characteristics, and limited ethnic diversity, as most participants were Caucasian. Tacrolimus maintains a strong efficacy-safety profile in adult kidney transplantation. Future studies with more diverse populations, standardized therapeutic drug monitoring, and longer follow-up durations are required to enhance generalizability and support individualized immunosuppressive management.